Barriers for nurses’ participation in and utilisation of clinical research in three hospitals within the Kumasi Metropolis, Ghana - Nkrumah, Isaac; Atuhaire, Catherine; Priebe, Gunilla; Cumber, Samuel Nambile (Pan African Medical Journal, 2018)
Introduction: Scientific research results are a necessary base for high quality nursing practice. The level of implementation of research in the clinical setting, including nurses' participation in and knowledge of research results, have gained considerable attention internationally. However, the remarkable international increase of such studies does not apply to the Ghanaian context. We therefore set out to evaluate the degree of involvement of nurses in research, as well as their utilization patterns of research findings in Ghana. Objectives: the study sought to investigate the proportion of nurses involved in clinical research as well as barriers for nurses' participation and utilization of research findings, within the Kumasi Metropolis area, Ghana. Methods: A descriptive and analytical cross-sectional study design was used in this study. A 47 item questionnaire elicited data on 158 participants' demographics, the proportion and the barriers to participation, which was then analyzed using SSPS version 17 software. Qualitative interviews with key informants complemented quantitative survey data. In-depth interviews with nurse managers at the hospitals in focus was conducted and analyzed thematically. Results: The study shows that 36.1% of the nurses, included in the study, had participated in research and only 25.3% of these had (knowingly) used specific research results in clinical practice. However, the level of research participation differed greatly between nurses working at different hospitals. Nurses' participation in clinical research was shown to be associated with their perception of benefit of research to practice as well as their understanding of time as a factor for them engaging in reading scientific articles. In addition, barriers associated with nurses' integration of research findings into the daily practice was their perceived lack of support from the collegium and their perception of research as not part of the nursing role. Conclusion: Findings from the study suggest that there is a need to create institutional support to facilitate and encourage nurses' participation in research, yet also to formalize nurses' continuous professional development. This, could change nurses' attitudes towards research, and contribute to improving health care as it would increase nurses' role as agents for evidence based clinical practice.
Keywords: Evidence based medicine; Nurses´ professional role; Delivery of health care; Clinical nursing research; Ghana health care sector